Investor Sensitivity to Liquidity and Systematic Risk in Indonesia's Real Estate Market - Teguh Prakoso; Rina Apriliani; Yulistina Yulistina; Donny Dharmawan; Nurnaningsih Utiarahman (Celebes Scholar pg, 2025)
The current paper analyzes whether the liquidity and systematic risk can predict stock returns not only as a typical financial indicator but as a kind of a descriptive tip in modern market environments. Using panel data of Indonesian firms listed in the property-sector in the Indonesia Stock Exchange, the research makes use of the random effects model of statistical analysis to assess how firms-level liquidity statistics, beta, and Return results are connected to one another. The findings show that the systematic risk has a strong and positive effect on the stock returns but this is not the case with liquidity, which does not have a similar type of effect. This result is not an indicator of the reduced role of economy but it is a significant rejuvenation concerning the methods in which financial information is being assimilated, ranked and acted upon by the investors. The lack of the effect of liquidity is said not to be irrelevant but invisible in platforms, stories, and investor attention schemes that are more and more dominating the interpretive access. By highlighting a changing ecology of valuation where the salience of financial metrics is mediated by visibility and volatility, as well as digital resonance, the findings help to understand that salience in this context has become contested, and the measured episodically as they become visible and volatile on the temporal shelf of valuation.